Pengaruh Preheat terhadap Sifat Mekanis Sambungan Metal Inert Gas (MIG) pada Baja Karbon Rendah - Wartono Wartono; Muhammad Taufiq; Abraham Julius (Proklamasi 45 University, 2019)
The objective of this research is to find out the effect of preheat on mechanical properties of the metal inert gas welding (MIG) on low carbon steel. The welding method uses a MIG welding on a low carbon steel strip plate specimen, in the V angle of 60°, using ER70S-6 electrode wire and CO2 for protection, the variable of this research is a preheat temperature of 100 oC, 200 oC, 300 oC and non-preheat. The test results showed that the highest Vickers hardness value is owned by the preheat 200 oC temperature with Vickers hardness value of 206.674 kg/mm2, the tensile test specimens with preheat 200 oC temperature variations have the greatest tensile strength is the average of 54.87 Kgf/mm2, the value of the highest impact energy on preheat 100 oC of 98.399 Joules.